Structural investigation and modelling insight of 2-butoxy-n-[2-(diethylamino)Ethyl] quinoline-4-carboxamide - J. DEVA ANBAN; SAYANTAN PRADHAN; C. JAMES (International Journal of Pharma and Bio Sciences, 2017)
In this study, the anesthetic compound 2-Butoxy-N-[2-(diethylamino) ethyl] quinoline-4-carboxamide (BDQ) was optimized with Density Functional Theory (DFT) calculations using B3LYP /6-311+G (d, p) basis set. FT-IR, FT-Raman and UV-visible spectra have been recorded and theoretical calculations were carried out with the aid of Normal Coordinate Analysis (NCA). Hyperconjugative interactions, revealed the stability of the molecule by Natural Bond Orbital (NBO) analysis. The presence of secondary amide increases the stability of the molecule. The biological significance of the molecule is enhanced by the π→π* interactions. Molecular docking studies were carried out to understand the binding of the molecule with the human voltage-gated sodium channels.